Jiwa yang merajut Nusantara - Gusman, Irman, 1962- (Jakarta : Ghalia Indonesia Pub., 2012)
Autobiography of Irman Gusman, the chairman of the Indonesian Regional Representatives Council.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Koleksi Sumbangan: Dr. Syed Husin Ali.
Keywords: Gusman, Irman, -- 1962-.; Indonesia. -- Dewan Perwakilan Daerah; Legislators -- Indonesia -- Biography